ESTRO IORT Task Force/ACROP recommendations for intraoperative radiation therapy in borderline-resected pancreatic cancer - Felipe A. Calvo; Jose M. Asencio; Falk Roeder; Robert Krempien; Philip Poortmans; Frank W. Hensley; Marco Krengli (Clinical and Translational Radiation Oncology, 2020)
Radiation therapy (RT) is a valuable component of multimodal treatment for localized pancreatic cancer. Intraoperative radiation therapy (IORT) is a very precise RT modality to intensify the irradiation effect for cancer involving upper abdominal structures and organs, generally delivered with electrons (IOERT). Unresectable, borderline and resectable disease categories benefit from dose-escalated chemoradiation strategies in the context of active systemic therapy and potential radical surgery. Prolonged preoperative treatment may act as a filter for selecting patients with occult resistant metastatic disease. Encouraging survival rates have been documented in patients treated with preoperative chemoradiation followed by radical surgery and IOERT (>20 months median survival, >35% survival at 3 years). Intensive preoperative treatment, including induction chemotherapy followed by chemoradiation and an IOERT boost, appears to prolong long-term survival within the subset of patients who remain relapse-free for>2 years (>30 months median survival; >40% survival at 3 years). Improvement of local control through higher RT doses has an impact on the survival of patients with a lower tendency towards disease spread. IOERT is a well-accepted approach in the clinical scenario (maturity and reproducibility of results), and extremely accurate in terms of dose-deposition characteristics and normal tissue sparing. The technique can be adapted to systemic therapy and surgical progress. International guidelines (National Comprehensive Cancer Network or NCCN guidelines) currently recommend use of IOERT in cases of close surgical margins and residual disease. We hereby report the ESTRO/ACROP recommendations for performing IOERT in borderline-resectable pancreatic cancer.